Coalition Building: What Happens When External Facilitators Put CBPR Principles in Practice? Ethnographic Examples from the Massachusetts HEALing Communities Study - Mari-Lynn Drainoni; Galya Walt; Linda Martinez; Rebecca Smeltzer; Savanna Santarpio; Rosie Munoz-Lopez; Craig McClay; Lauren Keisling; Aumani Harris; Faizah Gillen; Valerie El-Alfi; Erika Crable; et al. (The University of Alabama, 2023)
The HEALing Communities Study (HCS) is a large-scale multisite study testing community engagement using coalition facilitation as an approach to addressing the worsening overdose crisis. Within community engagement, community-based participatory research (CBPR) principles guide researchers on best practices for working in partnership with communities, yet these principles have not been well researched in large, complex, multisite studies. This paper uses ethnographic methods to explore how coalitions operationalized CBPR principles during early coalition formation. Two coders independently analyzed 101 ethnographies from HCS coalition meetings in eight Massachusetts communities held between November 2019 and December 2020. Themes were developed through consensus between the coders, followed by group discussions among the authorship team. We found that mutual trust, shared goals, addressing power dynamics, meeting structure, and attending to the sociopolitical community context are critical elements that can either hinder or advance the use of CBPR principles in practice. These findings provide unique suggestions for future community-engaged multisite studies, and demonstrate the importance of research teams mitigating inherent power imbalances by acknowledging and creating spaces for community ownership. The findings also highlight the value of a community engagement facilitator (CEF) role, as well as strategies like transparency, uniting over shared interests, and bringing in a wide range of stakeholders when operationalizing CBPR principles.